Real-time monitoring of personal exposures to carbon dioxide. (1st August 2016) - Gall, Elliott T.; Cheung, Toby; Luhung, Irvan; Schiavon, Stefano; Nazaroff, William W.
Abstract: Elevated indoor CO2 levels are indicative of insufficient ventilation in occupied spaces and correlate with elevated concentrations of pollutants of indoor origin. Adverse health and well-being outcomes associated with elevated indoor CO2 levels are based on CO2 as a proxy, although some emerging evidence suggests CO2 itself may impact human cognition. Using portable monitors, we conducted an exposure study with 16 subjects in Singapore to understand the levels, dynamics and influencing factors of personal exposure to CO2 . Participants carried a CO2 monitor continuously for 7-day periods recording their exposure levels at 1-min intervals. A recall diary was maintained of time-microenvironment-activity budget. We found that the mode of bedroom ventilation was a major determinant of CO2 exposure. Approximately half of the participants slept in bedrooms employing ductless split air-conditioners (group "AC"); half slept in bedrooms naturally ventilated through operable windows (group "NV"). Median CO2 exposure levels for AC vs. NV groups are significantly different ( x ˜ A C  = 650 ppm vs. x ˜ N V  = 550 ppm, p  < 0.001). Mean daily integrated exposures for group AC were statistically higher than for group NV: 22, 800 ppm h/d vs. 16, 000 ppm h/d ( p  < 0.005). Exposure events associated with potential adverse cognitive implications (duration > 2.5 h, average CO2 mixing ratio > 1000 ppm) occurred, on average, at frequencies of 0.5 d −1 across all participants, 0.6 d −1 for AC participants and 0.2 d −1 for NV participants. The majority of such events occurred in the home (86%), followed by work (9%) and transit (3%). Graphical abstract: Highlights: Elevated indoor CO2 correlates with adverse outcomes for health and well-being. Using personal monitors, we report time resolved personal CO2 exposure levels. 16 subjects participated for 1 week each; carried monitor during normal activities. CO2 exposure events with potential cognitive impacts occur 0.5/day for all subjects. Bedroom ventilation mode strongly influences CO2 integrated exposure.